Преторій у середньовічному Херсоні - Храпунов, М.І. (Археологія, 2002)
У статті проаналізовано значення терміна «преторій» (πραιτώριον), браму якого було споруджено у 1059 р. стратигом Херсона Левом Аліатом. Ймовірно, «преторієм» називали укріплення у північно-східній частині цього міста, тепер відоме як «цитадель». В статье анализируется вопрос о местонахождении «претория» в Херсоне. Император Феофил (829—842) учредил в Крыму новый военно-административный округ (фему) с центром в Херсоне. В юго-восточной части города находится укрепление, ныне именуемое «цитаделью». У стен этого укрепления обнаружена надпись 1059 г., указывающая на то, что здесь существовал «преторий», ворота которого были построены наместником (стратигом) фемы.
Слово πραιτώριον, по Гийу, в средние века обозначало цитадель, укрепление внутри города, центр византийской администрации.
Таким образом, анализ надписи XI в. позволяет определить, что в фемный период юго-восточная часть Херсона называлась преторием и что именно Херсон был столицей фемы. Отсюда византийская администрация осуществляла управление владениями империи в Крыму. The article analyses the question of the location of the Praetorian in Kherson. During the reign of Theophilus (829–842), the empire established a new administrative unit (theme) in Crimea, with the capital in Kherson. In the Southeastern part of the town, the fortification is called the "citadel". There is an inscription from 1059 according to which the governor (strategist) of the theme built an iron gate of the praetorian in Kherson.
During the Middle Ages, the word πραιτώριον by Gey defined the citadel as a fortification inside the town, a center of the Byzantine administration.
Thus, the analysis of the 11th-century inscription allows one to find out how the citadel of Kherson was called during the theme period and is one more evidence for the fact, that Kherson was the capital of the theme. From there, the Byzantine administration governed the imperial territories in Crimea.